The conserved sex regulator DMRT1 recruits SOX9 in sexual cell fate reprogramming. Issue 11 (7th June 2021) - Lindeman, Robin E; Murphy, Mark W; Agrimson, Kellie S; Gewiss, Rachel L; Bardwell, Vivian J; Gearhart, Micah D; Zarkower, David
Abstract: Mammalian sexual development commences when fetal bipotential progenitor cells adopt male Sertoli (in XY) or female granulosa (in XX) gonadal cell fates. Differentiation of these cells involves extensive divergence in chromatin state and gene expression, reflecting distinct roles in sexual differentiation and gametogenesis. Surprisingly, differentiated gonadal cell fates require active maintenance through postnatal life to prevent sexual transdifferentiation and female cell fate can be reprogrammed by ectopic expression of the sex regulator DMRT1. Here we examine how DMRT1 reprograms granulosa cells to Sertoli-like cells in vivo and in culture. We define postnatal sex-biased gene expression programs and identify three-dimensional chromatin contacts and differentially accessible chromatin regions (DARs) associated with differentially expressed genes. Using a conditional transgene we find DMRT1 only partially reprograms the ovarian transcriptome in the absence of SOX9 and its paralog SOX8, indicating that these factors functionally cooperate with DMRT1. ATAC-seq and ChIP-seq show that DMRT1 induces formation of many DARs that it binds with SOX9, and DMRT1 is required for binding of SOX9 at most of these. We suggest that DMRT1 can act as a pioneer factor to open chromatin and allow binding of SOX9, which then cooperates with DMRT1 to reprogram sexual cell fate.